Topic diagnostics of coronary pathology in coronary heart disease patients by contrast stress echocardiography with dipyridamole - S. T. Matskeplishvili; E. U. Asymbekova; E. A. Ayazyan; V. I. Ioshina; T. V. Kavtiashvili (Кардиоваскулярная терапия и профилактика)
Aim. To assess diagnostic potential of contrast stress echocardiography (CS-EchoCG) with dipyridamole in coronary heart disease (CHD) patients. Material and methods. The study included 22 patients (mean age 56.04±1.8 years) with typical CHD clinics. The results of traditional S-EchoCG and CS-EchoCG with dipyridamole were compared with coronaroangiography (CAG) data. Results. Both methods of EchoCG visualization were highly informative for topic diagnostics of coronary atherosclerosis – 91%, comparing with CAG results. CS-EchoCG had a number of benefits: sensitivity, specificity, and prognostic value, comparing to traditional S-EchoCG, were 95% and 75%, 95% and 86%, 50% and 91%, respectively. In CS-EchoCG, perfusion abnormalities were registered even with low dipyridamole doses. This allows to diagnose coronary blood flow disturbance before asynergic zones appear. Conclusion. CS-EchoCG with dipyridamole was highly predictive in coronary insufficiency diagnostics. The results of CS-EchoCG and CAG were comparable.